Cambios de costumbres, tradiciones y globalización que dan identidad en Machala, una mirada desde el arte - Arcentales Fernández, Dennys Tomas (2015)
For a better understanding of this research it has been divided into four chapters. Chapter one refers to the historical background of the term Melero with which certain longstanding santarroseños was called. Also globalization has influenced the loss of identity, also, art and anthropology of gender as a fundamental part to dispel doubts about the issue at hand. Chapter two presents the drawing as part of the proposal will address how this technology and make it work as work time, based on the concept of Harold Rosenberg.